An Analysis of SWOT to Improve Competitiveness of Coffee SMEs - Aulia Ernawati, Farah (Siber Journal of Transportation and Logistics, 2023)
SWOT analysis has become an important tool in planning business strategies, especially for coffee SMEs in Sidoarjo. By understanding their internal strengths, weaknesses, market opportunities and threats, SMEs can identify concrete steps to increase their competitiveness. By focusing on product quality development, market expansion, managerial skills training, product innovation, and industry collaboration, coffee SMEs can strengthen their position in local and regional markets. SWOT analysis provides an in-depth and holistic view of the internal and external factors that influence the growth and success of coffee SMEs, making it a very useful tool in strategic planning.